Analysis of the Digital Literacy Skills of Grade XI Senior High School Students in Online Biology Learning - Kusumawati, Balgis; Syafi’i, Wan; Daryanes, Febblina (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
The Covid-19 pandemic has made changes to several aspects of life such as education. Online learning is a new challenge for educators and students and mastery of using digital media is the key to successful education during a pandemic. This study aims to determine the digital literacy ability profile of class XI high school students in learning dare biology during the Covid-19 pandemic. The benefits of this research are providing knowledge and motivation for students, providing views and input for educators in developing learning strategies. This study used a descriptive quantitative method with instruments used in data collection in the form of validation sheets, questionnaire sheets and interview lists. The digital literacy component includes 8 digital literacy components. The results obtained on the functional skill component with an average of 86.91%, the creative component with an average of 77.79%, the average collaboration component is 71.07%, the ability to search for and select information with an average 77.10%, the critical thinking and evaluation component with an average of 76.20%, the socio-cultural understanding component with an average of 75.29%, the security component with an average of 84.82%. All of these components are known to mean that the average digital literacy ability of class XI students at SMA 3 Pekanbaru City gets a score of 78.81%. Based on these results, it can be interpreted that the Digital Literacy Ability of Class XI High School Students in Biology Online Learning during the Covid-19 Pandemic Period is in the Good category.